Bioaugmentation as an associated technology for bioremediation of soil contaminated with sulfentrazone - Melo, Christiane Augusta Diniz; Passos, Ana Beatriz Rocha de Jesus; Madalão, João Carlos; Silva, Daniel Valadão; Massenssini, André Marcos; Silva, Antônio Alberto da; Costa, Maurício Dutra; Souza, Matheus de Freitas (Ecological Indicators, 2019)
The association between remediation plants and bioenhancement with a bacterial consortium may improve the efficiency and accelerate the decontamination process of soils contaminated with herbicides. The objective of this work was to evaluate the potential for bioremediation of soils contaminated with sulfentrazone by using a previously selected bacterial consortium, namely, phytoremediator plants, and their combination. The treatments consisted of a single crop of Canavalia ensiformis, a single crop of Helianthus annuus, both species in mixed cultivation, tilled soil in association with the presence or absence of inoculation with a bacterial consortium and different bioremediation periods (25, 45, 65 and 85 days after thinning). At the end of each season, a bioassay was performed with the bioindicator species Sorghum bicolor, and the sulfentrazone residues were quantified in soil by high-performance liquid chromatography. The Helianthus annuus single crop and the mixed cultivation reduced by 64% the half-life of sulfentrazone in comparison to soil cultivated with C. ensiformis without inoculation and by 43% compared to the treatments composed of untilled soil and a single crop of C. ensiformis in the presence of inoculation, respectively. The mixed cultivation of C. ensiformis and H. annuus and the single crop of H. annuus, regardless of soil inoculation with the bacterial consortium, are the most efficient techniques of bioremediation of sulfentrazone in soil. Single-crop or mixed cultivation of these species on day 85 after thinning provides considerable reductions in the concentration of sulfentrazone in the soil; however, that period is not sufficient to allow the growth of the indicator plant without the occurrence of toxicity.
Keywords: Bioenhancement; Phytoremediation; Herbicide; Half-life time